Engineered multiple translation initiation sites: a novel tool to enhance protein production in Bacillus licheniformis and other industrially relevant bacteria. Issue 20 (16th November 2022) - Zhang, Manyu; Song, Jing; Xiao, Jun; Jin, Jingjie; Nomura, Christopher T; Chen, Shouwen; Wang, Qin
Abstract: Gram-positive bacteria are a nascent platform for synthetic biology and metabolic engineering that can provide new opportunities for the production of biomolecules. However, the lack of standardized methods and genetic parts is a major obstacle towards attaining the acceptance and widespread use of Gram-positive bacterial chassis for industrial bioproduction. In this study, we have engineered a novel mRNA leader sequence containing more than one ribosomal binding site (RBS) which could initiate translation from multiple sites, vastly enhancing the translation efficiency of the Gram-positive industrial strain Bacillus licheniformis . This is the first report elucidating the impact of more than one RBS to initiate translation and enhance protein output in B. licheniformis . We also explored the application of more than one RBS for both intracellular and extracellular protein production in B. licheniformis to demonstrate its efficiency, consistency and potential for biotechnological applications. Moreover, we applied these concepts for use in other industrially relevant Gram-positive bacteria, such as Bacillus subtilis and Corynebacterium glutamicum . In all, a highly efficient and robust broad-host expression element has been designed to strengthen and fine-tune the protein outputs for the use of bioproduction in microbial cell factories.